2022
DOI: 10.3389/fcell.2022.840513
|View full text |Cite
|
Sign up to set email alerts
|

Global Landscape of m6A Methylation of Differently Expressed Genes in Muscle Tissue of Liaoyu White Cattle and Simmental Cattle

Abstract: Liaoyu white cattle (LYWC) is a local breed in Liaoning Province, China. It has the advantages of grow quickly, high slaughter ratew, high meat quality and strong anti-stress ability. N6 methyladenosine (m6A) is a methylation modification of N6 position of RNA adenine, which is an important modification mechanism affecting physiological phenomena. In this study, we used the longissimus dorsi muscle of LYWC and SIMC for m6A-seq and RNA-seq high-throughput sequencing, and identified the key genes involved in mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Tao X et al used m6A sequencing to identify that m6A-modified genes of wild boar—Landrace and Rongchang pigs—were breed specific in longissimus dorsi (LD), and exerted different physiological functions in different breeds [ 25 ]. Dang Y et al found by m6A-Seq that m6A modification was involved in the growth and development of beef cattle LD tissue, and the differentially expressed m6A genes were mainly involved in skeletal muscle contraction, steroid biosynthesis process and REDOX process [ 26 ]. Petrosino JM et al discovered that the skeletal muscle size of mice during hypertrophy was related to the increase in METTL3 and m6A levels [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tao X et al used m6A sequencing to identify that m6A-modified genes of wild boar—Landrace and Rongchang pigs—were breed specific in longissimus dorsi (LD), and exerted different physiological functions in different breeds [ 25 ]. Dang Y et al found by m6A-Seq that m6A modification was involved in the growth and development of beef cattle LD tissue, and the differentially expressed m6A genes were mainly involved in skeletal muscle contraction, steroid biosynthesis process and REDOX process [ 26 ]. Petrosino JM et al discovered that the skeletal muscle size of mice during hypertrophy was related to the increase in METTL3 and m6A levels [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…( 13 ) explored the involvement of m6A mRNA modifications in mediating muscle regulation. Dang et al ( 14 ) identified the key genes involved in cattle muscle growth and m6A modification development by bioinformatics analysis. The results showed that the differentially expressed genes modified by m6A are mainly involved in skeletal muscle contraction, steroid biosynthesis, redox process, the PPAR pathway, and fatty acid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…N6-methyladenosine (m 6 A) modification of RNA refers to A methylation modification of the adenine (A) 6-position nitrogen atom catalyzed by methyltransferase, which was first discovered in the 1970s. [1][2][3] It is similar to DNA or histone methylation in that m 6 A modification has an impact on RNA metabolism, function, and localization. 1,4,5 More than 150 post-transcriptional modifications are known to modify RNA at its four nucleotides (A, G, C, and U).…”
Section: Introductionmentioning
confidence: 99%